Tax Compliance and Investment Incentives: Firm Responses to Accelerated Depreciation in China - Fan, Ziying; Liu, Yu (Journal of economic behavior & organization, 2020)
We evaluate the effects of a Chinese accelerated depreciation policy that occurred in 2014 on firm investment. We present three findings. First, on average, the policy increased firms’ investment in eligible capital, especially the purchase of equipment and machines. Second, the policy effects are stronger for larger firms, firms with more cash, and firms with better access to finance, which tend to be less financially constrained but have better tax compliance. Third, the effect magnitude increases with imputed county tax enforcement but decreases with provincial tax fraud rate. These results shed light on the importance of improving tax compliance in making tax incentives effective.